HUBUNGAN TINGKAT EKONOMI KELUARGA DENGAN HASIL BELAJAR SISWA - Baiq Nana Apriani; Nuraeni Nuraeni; M. Chairul Anam (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
ABSTRACT Family socioeconomic status is an external factor that can influence students’ learning outcomes, particularly in terms of access to learning facilities and educational support. This study aims to determine the relationship between family socioeconomic status and students’ learning outcomes at SMPN 1 Praya Barat Daya in the 2020/2021 academic year. This study employed a quantitative approach with an ex post facto correlational design. The population consisted of 107 students in grades VIII and IX, all of whom were selected as the sample using a population study technique. Data on family socioeconomic status were collected using a Likert-scale questionnaire based on indicators of income, parents’ educational level, and ownership of learning facilities, while data on learning outcomes were obtained from students’ report card scores. Data were analyzed using the Pearson Product Moment correlation. The results showed that the calculated was greater than the table value at a 5% significance level. This indicates a positive and significant relationship between family socioeconomic status and students’ learning outcomes, with a strong correlation level. The coefficient of determination of 51.7% indicates the contribution of family socioeconomic status to students’ learning outcomes. ABSTRAK Kondisi sosial ekonomi keluarga merupakan faktor eksternal yang dapat memengaruhi hasil belajar siswa, terutama dalam hal ketersediaan fasilitas dan dukungan pendidikan. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat ekonomi keluarga dengan hasil belajar siswa di SMPN 1 Praya Barat Daya Tahun Pelajaran 2020/2021. Penelitian ini menggunakan pendekatan kuantitatif dengan desain ex post facto korelasional. Populasi penelitian berjumlah 107 siswa kelas VIII dan IX, yang seluruhnya dijadikan sampel melalui teknik studi populasi. Data tingkat ekonomi keluarga dikumpulkan menggunakan angket skala Likert berdasarkan indikator pendapatan, pendidikan orang tua, dan fasilitas belajar, sedangkan data hasil belajar diperoleh dari nilai rapor. Analisis data menggunakan korelasi Product Moment Pearson. Hasil penelitian menunjukkan bahwa nilai lebih besar dari pada taraf signifikansi 5%. Hal ini menunjukkan adanya hubungan positif dan signifikan antara tingkat ekonomi keluarga dengan hasil belajar siswa dengan kekuatan korelasi kategori kuat. Koefisien determinasi sebesar 51,7% menunjukkan kontribusi tingkat ekonomi keluarga terhadap hasil belajar siswa.